2017
DOI: 10.1088/2053-1583/aa5481
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic patterned growth of high-mobility large-crystal graphene: a path towards wafer scale integration

Abstract: IntroductionCVD synthesis of graphene on catalytically-active substrates has emerged as the most promising approach for large-area production of graphene [1] . The self-limiting nature of CVD growth on metals such as copper (Cu) and platinum allows synthesis of large-scale homogeneous films of monolayer graphene. However, electrical characterization of polycrystalline samples of CVD graphene reveals that the presence of grain boundaries causes significant degradation of the electric performance, compared to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
130
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 77 publications
(133 citation statements)
references
References 31 publications
(70 reference statements)
2
130
0
Order By: Relevance
“…2D growth has already been clearly demonstrated for graphene on copper . Deterministic nucleation and growth of graphene on copper (see Figure b) has also been demonstrated to yield graphene single crystals . This process may require edge functionalization for graphene growth on noncatalytic surfaces.…”
Section: D Materials: Production and Processingmentioning
confidence: 87%
“…2D growth has already been clearly demonstrated for graphene on copper . Deterministic nucleation and growth of graphene on copper (see Figure b) has also been demonstrated to yield graphene single crystals . This process may require edge functionalization for graphene growth on noncatalytic surfaces.…”
Section: D Materials: Production and Processingmentioning
confidence: 87%
“…Moreover, a few works have suggested the possibility of a highly selective growth mechanism, strongly favoring the AB and 30°-rotated stacking over random twisting [16,17]. We found that our CVD process for isolated graphene single crystals [18,19] yields large-area bilayers with AB or QC-TBG configurations exclusively. The two types can be easily distinguished on the basis of the relative orientations of the hexagonal edges of the two layers, allowing for large-scale production of QC-TBG, transfer to arbitrary substrates and device processing.…”
mentioning
confidence: 81%
“…The used method allows a low level of metal contamination during the graphene delamination from the growth substrate as well as damage-free lamination onto the target substrate. A matrix of graphene crystals with 200 µm spacing and 150 µm crystal size was grown on Cu foils using chromium (Cr) nucleation seeds [22]. Cu foils were patterned with nucleation seeds using optical lithography and evaporation of 25 nm of Cr.…”
Section: Fabricationmentioning
confidence: 99%